Outcomes of ureteral stent placement for hydronephrosis in patients with ureteral stone - Widyokirono, Dyah Ratih; Kloping, Yudhistira Pradnyan; Rahman, Zakaria Aulia; Hakim, Lukman (Universa Medicina, 2021)
BackgroundRoutine ureteral stent placement after ureteroscopy (URS) for ureteral stone treatment is arguable due to the possible stent-related symptoms. Several studies claimed that its use is necessary, while others reported that its use is excessive. Hydronephrosis occurs when urine cannot drain out from the kidney to the bladder due to blockage or obstruction. We aimed to evaluate the role of ureteral stents in hydronephrosis resolution in ureteral stone patients following URS lithotripsy. MethodsThis was a prospective observational study using secondary data involving 130 ureteral stone patients undergoing URS lithotripsy [99 patients (76.2%) with stent placement and 31 patients (23.8%) without stent]. Data consisting of baseline characteristics, pre-operative status, intraoperative characteristics, and postoperative complications were collected from the medical record database and presented descriptively. The patients were divided into two groups based on stent placement. Comparison of hydronephrosis resolution between the groups was analyzed with Chi-square. ResultsUreteral lesions were the most common indication of ureteral stent placement following URS lithotripsy (28.3%). The most bothersome symptoms were dysuria in 18 patients (18.2%); followed by frequency in eight patients (8.1%) and low back pain in six patients (6.1%). All symptoms were successfully treated with oral medications. There were 41 patients (91.1%) with pre-operative hydronephrosis significantly resolved after stent placement compared to 5 (62.5%) patients without stent placement (p=0.027). ConclusionUreteral stenting significantly resolves pre-operative hydronephrosis after URS lithotripsy in patients with ureteral stone. Ureteral stent placement is the preferred method for the treatment of pre-operative hydronephrosis.